Progressive pseudorheumatoid dysplasia misdiagnosed as juvenile idiopathic arthritis: a case report - Anjumanara Anver Omar (BMC, 2021)
Abstract Background Progressive pseudorheumatoid dysplasia is a rare, autosomal recessively inherited, noninflammatory musculoskeletal disorder caused by mutations occurring in the WNT1-inducible signaling pathway protein 3 gene. Joint cartilage is the primary site of involvement, leading to arthralgia, joint stiffness, contractures, enlargement of the epiphyses and metaphysis of the hand joints, spinal abnormalities, short stature, early osteoarthritis, and osteoporosis. Juvenile idiopathic arthritis is the most common chronic rheumatic disease in childhood and has unknown etiology. Clinical features of progressive pseudorheumatoid dysplasia resemble those of juvenile idiopathic arthritis. Patients with progressive pseudorheumatoid dysplasia are usually misdiagnosed as having juvenile idiopathic arthritis. Case presentation A 13-year-old Yemeni female presented to the rheumatology clinic with a history of joint pains, bone pains, and bone deformity for 7 years. Weight and height were below the third percentiles. There was no tender swelling of metacarpophalangeal and interphalangeal joints, and she presented with scoliosis. Radiographs of the hands revealed the widening of the epiphyses. Progressive pseudorheumatoid dysplasia was suspected, and genetic testing for WNT1-inducible signaling pathway protein 1, 2, and 3 was requested with these findings. A homozygous, likely pathogenic variant was identified in the WNT1-inducible signaling pathway protein 3 gene, which confirmed our diagnosis. Conclusion Progressive pseudorheumatoid dysplasia is a rare form of spondyloepimetaphyseal dysplasia and is clinically misdiagnosed as juvenile idiopathic arthritis. It is crucial to consider progressive pseudorheumatoid dysplasia, especially in patients with standard inflammatory markers who are being followed up for juvenile idiopathic arthritis and not improving with antirheumatic intervention.